Modeling Oral Reading Fluency Development in Latino Students: A Longitudinal Study Across Second and Third Grade - Al Otaiba, Stephanie (2009)
This study examines growth in oral reading fluency across 2nd and 3rd grade for Latino students grouped in 3 English proficiency levels: students receiving English as a second language (ESL) services (n = 2,182), students exited from ESL services (n = 965), and students never designated as needing services (n = 1,857). An important focus was to learn whether, within these 3 groups, proficiency levels and growth were reliably related to special education status. Using hierarchical linear modeling, the authors compared proficiency levels and growth in oral reading fluency in English between and within groups and then to state reading benchmarks. Findings indicate that oral reading fluency scores reliably distinguished between students with learning disabilities and typically developing students within each group (effect sizes ranging from 0.96 to 1.51). The growth trajectory included a significant quadratic trend (generally slowing over time). These findings support the effectiveness of using oral reading fluency in English to screen and monitor reading progress under Response to Intervention models, but also suggest caution in interpreting oral reading fluency data as part of the process in identifying students with learning disabilities.